Given equation ---›
2x + 7y = 4 (1st equation)
-4x - 3y = 14 (2nd equation)
Multiply 1st equation by 2 and then add it by second equation
![= > 2(2x + 7y = 4) \\ \: \: \: \: \: \: \: \: + ( - 4x - 3y = 14) \\ \\ = > 4x + 14y = 8 \\ \: \: \: \: \: - 4x - 3y = 14 \\ \\ = > 11y = 22 \\ \\ = > y = 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/oocg839oyxl9s3hwl3esmtdnojipp51ltq.png)
So,
We get the value of y = 2
Now,,
![= > 2x + 7y = 4 \\ \\ = > 2x + 7(2) = 4 \\ \\ = > 2x = 4 - 14 \\ \\ = > 2x = - 10 \\ \\ = > x = - 5](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qwtih407zpz21ns09azphzwtwh6rv1tnvv.png)
Therefore value of x = -5.
Expressing the answer as an ordered pair in the format (a,b) => (-5, 2)